2024
DOI: 10.1186/s12910-024-01011-5
|View full text |Cite
|
Sign up to set email alerts
|

“That’s just Future Medicine” - a qualitative study on users’ experiences of symptom checker apps

Regina Müller,
Malte Klemmt,
Roland Koch
et al.

Abstract: Background Symptom checker apps (SCAs) are mobile or online applications for lay people that usually have two main functions: symptom analysis and recommendations. SCAs ask users questions about their symptoms via a chatbot, give a list with possible causes, and provide a recommendation, such as seeing a physician. However, it is unclear whether the actual performance of a SCA corresponds to the users’ experiences. This qualitative study investigates the subjective perspectives of SCA users to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This association with user satisfaction indicates that users' expectations also play a role in how they validate the app [40]. In a substudy of the CHECK.APP project, Müller distinguished between user expectations and motivations for app use and found that these factors play a role in SCA use [34]. In fact, according to Kopka's sample, 33% of SCA users reported that SCA's usefulness varied [52].…”
Section: Satisfaction With App Usementioning
confidence: 99%
See 4 more Smart Citations
“…This association with user satisfaction indicates that users' expectations also play a role in how they validate the app [40]. In a substudy of the CHECK.APP project, Müller distinguished between user expectations and motivations for app use and found that these factors play a role in SCA use [34]. In fact, according to Kopka's sample, 33% of SCA users reported that SCA's usefulness varied [52].…”
Section: Satisfaction With App Usementioning
confidence: 99%
“…a health symptom), laypersons enter health-related information into the SCA. Curiosity about one's health status or the desire to rule out possibly dangerous conditions, the availability of health care services, trust in SCA as well as certain symptoms are known factors associated with SCA use [2,8,10,[32][33][34][35][36]. Further engaging with SCA warrants distinct user experiences that are shaped by the confidence in one's ability for selfassessment [8][9][10]34], personal illness experiences [2,8,9], proficiency in navigating informational sources [8,9], age [32,37] and the ability to process and understand health-related information [1,[8][9][10]37], all of which are part of the abovementioned concepts.…”
Section: An Interface Between Ehealth Health Literacy and Health-rela...mentioning
confidence: 99%
See 3 more Smart Citations